Improving English Learning Outcomes of Students at Class XI IPA 1 1 in SMA Negeri 1 Lawa Through Interview Learning Model - Fisa, La (Journal of Teaching of English, 2021)
The purpose of this research is to improve the learning outcomes of the English language learning material on the expression of asking and giving opinion by applying the interview learning model. This research uses Classroom Action Research (CAR) which is carried out in two cycles with four stages, namely planning, action, observation, and reflection. The subjects in this study were students of class XI IPA 1.1 SMA Negeri 1 Lawa in semester 1 of the 2020/2021 academic year. The research instrument is a written test. Data analysis used descriptive analysis technique of comparison with percentage. The results of this study indicate that there is an increase in students' motivation and learning outcomes in the expression of asking and giving opinion in English as seen from the average score. The average score of increasing motivation and learning outcomes in English for the expression of asking and giving opinion through the use of the interview learning model is shown at the average value of the initial state of learning achievement in the pre-cycle the average value is 59.81, in the Cycle I it increases to 69 .63 and in the Cycle II increased with an average value of 82.41. In terms of minimum completeness criteria (KKM) in the initial observation (pre-cycle) students who achieved the KKM were 40.74%, in the Cycle I it increased to 55.56% and in the Cycle II it increased to 85.19%. The conclusion that can be drawn from this research is that there is an increase in English learning outcomes in the expression of asking and giving opinion material with the use of the interview learning model which has increased significantly, so it is feasible to be applied in SMA Negeri 1 Lawa.